Mikrostruktur dan Kekerasan Sambungan Pengelasan Gesek Disimilar Pipa Tembaga/Kuningan (Cu/Cu-Zn) - Nugroho, Aris Widyo; Suwanda, Totok; Serena, Septian Aldo (Semesta Teknika, 2016)
This study is focused on the influence of friction time on the microstructure and the hardness values of butt welded dissimilar pure copper/brass alloy pipes by continuous drive friction welding. Five variation of friction times were applied during the welding processes. The joint were evaluated by microstructural analysis and microhardness measurements. The results show that three distincs region were observed. The grain formation in the three regions were revealed. It was found that the hardness of the joints especially in HAZ regions were lower than that of the copper and brass base metals, while the hardness of the TMAZ region was higher than that of the copper base metal and the brass base metal. The microhardness values in the TMAZ increased with increasing the friction time up to 30 s and then decreased with incresing friction time.